Design and build a digital TV receiver double biquad antenna for the Greater Malang region and its surroundings - Waluyo Waluyo; Koesmarijanto Koesmarijanto; Lis Diana Mustafa (Politeknik Negeri Malang, 2022)
Many types of antennas can be used for digital TV receivers; in this article we try to design a double biquad antenna. This is due to a simple form, easy to make, a wide beamwidth. In designing a digital TV receiver for the Malang area, an STB device is needed, so that analog TV can still receive digital TV broadcasts. In this study, the antenna is made of copper wire, each side length: ¼ ? , with a working frequency: 650 MHz. In order to match the impedance of the 75? coaxial cable with the antenna, a balun 4:1 is required. The research place is in the Polinema Telecommunications laboratory. The test results show that the lowest return loss (RL) occurs at a frequency of F=605 MHz, namely RL: -17.8 dB, for a frequency of F=650 MHz, the magnitude of RL: -11.3 dB. The large VSWR antenna at the working frequency F: 650 MHz is 1.46. So that it can be said that it has fulfilled the antenna parameters, namely VSWR < 2. It means that there is a power loss of less than 10%. The largest antenna gain occurs at a frequency: 400 MHz namely: 14.85 dB,. While the average gain of the antenna is 2.21 dB. The antenna radiation pattern is omni directional. The double biquad antenna is very good for use as a digital TV receiver for the Greater Malang area, either without using a reflector or with a reflector.